Factors Influencing the Incidence of Stunting in Children at Tilamuta Community Health Center - Ayu Rahayu; Sulistiyah Sulistiyah; Tut Rayani Aksohini (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
Stunting is a major health concern in many developing countries, including Indonesia, with profound long-term effects on children’s physical, cognitive, and emotional development. This condition is primarily influenced by factors such as malnutrition, infections, and inadequate care during the first few years of life. The objective of this study was to analyze the factors associated with stunting in children under five years old within the working area of Puskesmas Tilamuta. An analytical survey design was employed, using a cross-sectional approach to examine 54 children, who were selected using accidental sampling. Data collection involved assessing factors such as exclusive breastfeeding, complementary feeding practices (MP-ASI), and low birth weight (BBLR). Statistical analysis was conducted using the Chi-Square test with Fisher's exact test to determine the association between these factors and stunting. The results revealed that exclusive breastfeeding had a significant impact on the occurrence of stunting, with a p-value of 0.002, suggesting that children who were exclusively breastfed were less likely to experience stunting. Similarly, the provision of complementary feeding (MP-ASI) was significantly associated with stunting (p = 0.043), highlighting the importance of timely and adequate complementary feeding to prevent stunting. However, the factor of low birth weight (BBLR) was found to have no significant effect on stunting (p = 0.202), indicating that other factors, such as nutrition and feeding practices, may have a more direct influence on stunting in the studied population. This study underscores the critical role of exclusive breastfeeding and proper complementary feeding practices in preventing stunting. It also suggests that addressing these factors, along with other local health interventions, may help reduce the incidence of stunting in children under five years old in the area.